The age of clusters and its influence on their activity preferences - Jirčikova, Eva; Pavelkova, Drahomíra; Bialic-Davendra, Magdalena; Homolka, Lubor (Technological and Economic Development of Economy, 2013)
The aim of this paper is to determine whether there exist age dependent differences in the orientation of clusters’ activities. The literature depicts different approaches to the cluster evolution process, highlighting that clusters are subject to a life cycle that emphasizes different sets of activities in various stages of their development. These activities appear to follow a certain trajectory, whereby the successful completion of initial less-intensive activities stimulates a shift in focus to more demanding, long-term projects. The presented research verifies that clusters can pass through different stages of development, and examines in detail their preferences for jointly-undertaken activities. Research, conducted on a sample of clusters of different countries and ages, was carried out through the use of questionnaires and structured interviews with cluster managers. It is a sample of so-called organized clusters, which have their own internal structure and which are characterized by conscious development. The study identified common cluster activities in the following areas: networking, human resources, research and innovations, business cooperation and promotion, support activities, lobbying, etc. The preference of their implementation was also ascertained. In addition, the analyzed sample was divided into two categories according to cluster age, allowing for a comparison and differentiation of the level of implementation of joint activities between embryonic and established clusters. The evaluation of this research demonstrated that in the selected groups of activities, there was a statistically significant difference in terms of their level of implementation in clusters of various ages.